The Influence of Transformational Leadership and Knowledge Manage-ment on Employee Creativity at PT Suri Tani Pemuka Lampung - Wardah Hany Afifah; Habibullah Jimad; Nova Mardiana (Lembaga Pengembangan Kinerja Dosen, 2025)
Employee creativity plays a vital role in en5suring organizational success, particularly in the face of growing industrial competition. PT. Suri Tani Pemuka Lampung, operating in the aquaculture sector, must cultivate a workforce that is both creative and adaptable to change. However, enhancing employee creativity remains a challenge. This study investigates the influence of transformational leadership and knowledge management on employee creativity at PT. Suri Tani Pemuka Lampung. Using a quantitative approach, data were collected from 210 permanent employees across various divisions through a structured questionnaire. The data were analyzed using multiple linear regression with SPSS. The findings reveal that both transformational leadership and knowledge management have a positive and significant impact on employee creativity, with knowledge management showing a more dominant effect. The study implies that to boost employee creativity, organizations must strengthen their knowledge management systems—particularly in terms of documentation, training, and knowledge sharing. Furthermore, leaders should adopt an open, inclusive leadership style that nurtures creativity and supports employees in developing their innovative potential.